2021
DOI: 10.1038/s41443-021-00483-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SARS CoV-2, COVID-19, and its vaccines on male sexual health and reproduction: where do we stand?

Abstract: Since severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was first discovered, there have been questions surrounding the effects of coronavirus disease 2019 (COVID-19), and more recently the COVID-19 vaccine, on men’s health and fertility. Significant research has been conducted to study viral tropism, potential causes for gender susceptibility, the impact of COVID-19 on male sexual function in the acute and recovery phases, and the effects of the virus on male reproductive organs and hormones. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…It is important to note that none of the studies reported the association of the COVID-19 vaccine with male and female reproductive health. There have been concerns among the public about the impact of vaccines on sperm and infertility, mainly driven by vocal conspiracy theorists [33]. Lifshitz et al investigated the impact of the Pfizer vaccine on the semen analysis parameters and found these parameters within the normal limit among vaccinated men, strengthening the notion that Pfizer's vaccine is safe among males [34].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that none of the studies reported the association of the COVID-19 vaccine with male and female reproductive health. There have been concerns among the public about the impact of vaccines on sperm and infertility, mainly driven by vocal conspiracy theorists [33]. Lifshitz et al investigated the impact of the Pfizer vaccine on the semen analysis parameters and found these parameters within the normal limit among vaccinated men, strengthening the notion that Pfizer's vaccine is safe among males [34].…”
Section: Discussionmentioning
confidence: 99%
“…While a recent study found that the incidence of urologic AEFIs following administration of the BNT162b2 vaccine was 0.7%, erectile impairment was not among these events [ 15 ]. To date, the impact of the vaccines on fertility, sperm production, or sexual function has not been assessed or compared across vaccines [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting results regarding the impact of COVID-19 infection on semen quality have been reported ( 137 ). As ACE2 is expressed in spermatogonia and Sertoli and Leydig cells ( 138 ), there was concern about the fact that the virus could affect male fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Original studies included about 500 semen analyses from men infected with SARS-CoV-2, and some alterations were found in approximatively one third of cases, especially in patients with severe COVID-19 ( 138 ). Hence, these findings elicited some concern also about the possible role of COVID-19 vaccination on male fertility ( 137 , 139 ). However, according to the published data, overall, no significant adverse effects of COVID-19 vaccines on male fertility have been reported so far, and no detrimental effect on both semen quality and fertility outcomes were observed in healthy donors ( 93 , 95 , 98 , 99 , 101 ), infertile men ( 94 , 96 ) and couples undergoing assisted reproduction treatments ( 103 , 104 ) or trying to conceive naturally ( 106 ).…”
Section: Discussionmentioning
confidence: 99%